Through a circular time: "ennui" and time in "La Regenta" and "Madame Bovary" - Núñez Puente, Sonia (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
During the second half of the nineteenth century a new philosophical-oriented phenomenon emerges: the ennui embodied in the feminine character. The issue of the ennui is brought up at the center of a new sense of temporality. Time is conceived as a kind of circular construction leading, invariably, to boredom as represented in the femenime figure. Leopoldo Alas "Clarín" and Gustave Flaubert in La Regenta and Madame Bovary create a prototype which exemplifies the ennui’s corrosive nature in the Nineteenth Century European literature.